Prehospital cardiopulmonary resuscitation duration and neurological outcome after out-of-hospital cardiac arrest among children by location of arrest: a Nationwide cohort study - Shida, Haruka; Matsuyama, Tasuku; Kiyohara, Kosuke; Kitamura, Tetsuhisa; Kishimori, Takefumi; Kiguchi, Takeyuki; Nishiyama, Chika; Kobayashi, Daisuke; Okabayashi, Satoe; Shimamoto, Tomonari; Kawamura, Takashi; Iwami, Taku (Scandinavian journal of trauma, resuscitation and emergency medicine, 2019)
Background Little is known about the associations between the duration of prehospital cardiopulmonary resuscitation (CPR) by emergency medical services (EMS) and outcomes among paediatric patients with out-of-hospital cardiac arrests (OHCAs). We investigated these associations and the optimal prehospital EMS CPR duration by the location of arrests. Methods We included paediatric patients aged 0–17 years with OHCAs before EMS arrival who were transported to medical institutions after resuscitation by bystanders or EMS personnel. We excluded paediatric OHCA patients for whom CPR was not performed, who had cardiac arrest after EMS arrival, whose EMS CPR duration were < 0 min or ≥120 min and who had cardiac arrest in healthcare facilities. Prehospital EMS CPR duration was defined as the time from CPR initiation by EMS personnel to the time of prehospital return of spontaneous circulation or to the time of hospital arrival. The primary outcome was 1-month survival with a favourable neurological outcome (cerebral performance category scale 1 or 2). Statistical analysis was performed with Mann-Whitney U tests for numerical variables and chi-squared test for categorical variables. Univariable and multivariable logistic regression analyses were applied to assess the association between prehospital EMS CPR duration and a favourable neurological outcome, and crude and adjusted odds ratios and their 95% confidence intervals were calculated. Results The proportion of patients with a favourable neurological outcome was lower in residential locations than in public locations (2.3% [66/2865] vs 10.8% [113/1048]; P < .001). In both univariable and multivariable logistic regression analyses, the proportion of patients with a favourable neurological outcome decreased as prehospital EMS CPR duration increased, regardless of the location of arrests ( P for trend <.001). However, some patients achieved a favourable neurological outcome after a prolonged prehospital EMS CPR duration (> 30 min) in both groups (1.4% [6/417] in residential locations and 0.6% [1/170] in public locations). Conclusions A longer prehospital EMS CPR duration is independently associated with a lower proportion of patients with a favourable neurological outcome. The association between prehospital EMS CPR duration and neurological outcome differed significantly by location of arrests.